Efficacy and safety of intravenous ferric carboxymaltose in the treatment of Restless Legs Syndrome: a systematic review and meta-analysis - Ayesha Khan; Harsh Kumar; Kuldeep Dalpat Rai; Anzel Saeed; Jawad Ishtiaq; Muhammad Tanveer Alam; Sakshi Chawla; Md Ariful Haque; Md Ariful Haque (Frontiers in Neurology)
IntroductionRestless Legs Syndrome (RLS), also known as Willis-Ekbom Disease (WED), is a sensorimotor disorder characterized by an uncontrollable urge to move the legs, typically accompanied by discomfort. Low iron levels, pregnancy, and age are some identified risk factors. RLS is treated using various pharmacological options, including dopamine agonists, benzodiazepines, anticonvulsants, opioids, and bupropion. Iron supplementation, particularly with intravenous Ferric carboxymaltose (FCM), has gained attention due to the role of iron deficiency in RLS pathophysiology. This meta-analysis evaluates the efficacy and safety of FCM in treating RLS symptoms.Materials and methodsA systematic review and meta-analysis were conducted following the PRISMA guidelines, using databases such as PubMed, Google Scholar, and Cochrane. Studies involving intravenous FCM in patients diagnosed with RLS were included. Statistical analysis was performed using Review Manager 5.4.ResultsSeven studies involving 539 participants were analyzed. FCM significantly reduced IRLS scores (WMD = −5.77; 95% CI = [−8.85, −2.70]; p = 0.0002) and improved VAS and SF-36 scores compared to placebo. However, FCM did not significantly improve RLS quality of life scores. Adverse events were more common in the FCM group, particularly nausea, but no significant differences were found for severe adverse events.ConclusionIn conclusion, intravenous ferric carboxymaltose significantly reduces Restless Legs Syndrome symptoms, especially in patients with confirmed iron deficiency. The treatment appears generally well-tolerated, with adverse effects being manageable. However, further long-term studies are needed to fully assess the safety profile and confirm sustained symptom improvement in a broader population.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier: CRD42024585233.